Atmospheric cold plasma inactivation of aerobic microorganisms on blueberries and effects on quality attributes. (April 2015) - Lacombe, Alison; Niemira, Brendan A.; Gurtler, Joshua B.; Fan, Xuetong; Sites, Joseph; Boyd, Glenn; Chen, Haiqiang
Abstract: Cold plasma (CP) is a novel nonthermal technology, potentially useful in food processing settings. Berries were treated with atmospheric CP for 0, 15, 30, 45, 60, 90, or 120 s at a working distance of 7.5 cm with a mixture of 4 cubic feet/minute (cfm) of CP jet and 7 cfm of ambient air. Blueberries were sampled for total aerobic plate count (APC) and yeast/molds immediately after treatment and at 1, 2, and 7 days. Blueberries were also analyzed for compression firmness, surface color, and total anthocyanins immediately after each treatment. All treatments with CP significantly ( P  < 0.05) reduced APC after exposure, with reductions ranging from 0.8 to 1.6 log CFU/g and 1.5 to 2.0 log CFU/g compared to the control after 1 and 7 days, respectively. Treatments longer than 60 s resulted in significant reductions in firmness, although it was demonstrated that collisions between the berries and the container contributed significantly to softening. A significant reduction in anthocyanins was observed after 90 s. The surface color measurements were significantly impacted after 120 s for the L * and a * values and 45 s for the b * values. CP can inactivate microorganisms on blueberries and could be optimized to improve the safety and quality of produce. Highlights: Cold plasma can nonthermally inactivate potential spoilage microorganisms. 30 s of treatment resulted in significant suppression of APC. Effective cold plasma treatments (45 s) had minimal impact on berry quality. Industry can use optimized cold plasma treatments on multiple types of produce.